Burden of Bites by Dogs and Other Animals in Los Angeles County, California, 2009-2011. (November 2016) - Lyu, Caleb; Jewell, Mirna Ponce; Piron, Jennifer; Ehnert, Karen; Beeler, Emily; Swanson, Alexandra; Smith, Lisa V.; Kuo, Tony
Objectives: The objective of this study was to analyze all animal-to-human bite reports during a 3-year period from a regional surveillance database. Results helped to inform local efforts to reduce and prevent animal-to-human bites. Methods: We reviewed all cases of animal-to-human bites occurring from 2009 through 2011 that were reported to the Los Angeles County Department of Public Health's Animal Bites Database. We collected data on the bite victim's date of birth, age, and address; bite circumstances (ie, date, time, location, how bite occurred); anatomic site and treatment of bite; type of reporting facility; and breed and management of biting animal. Results: From 2009 through 2011, 26 169 animal-to-human bites were reported, of which 23 103 (88%) were dog bites. Most animal-to-human bites (n = 7673, 29%) occurred between 4pm and 8pm and peaked during the month of July (n = 2663, 10%). Most animal-to-human bites occurred outdoors (n = 8772, 34%) and while victims engaged in recreational activities (n = 4353, 17%). The hands were the most common injury site (n = 9130, 35%), and only 1% of animal bites (n = 267) resulted in hospitalization. A total of 4115 bite victims (16%) received tetanus vaccinations. Of all animal-to-human bite cases, medical organizations reported 13 451 (51%), and animal control agencies reported 10 682 (41%). Conclusions: Animal-to-human bites can often lead to medical complications. Surveillance is essential in helping to identify, manage, and reduce these highly preventable injuries and direct public health actions and policies on animal bite risk and prevention.